PENGEMBANGAN BUKU AJAR BERBASIS PERMAINAN EDUKATIF KETERAMPILAN BERBICARA BAHASA ARAB BAGI SISWA MA BAHRUL ULUM DI JOMBANG - Siti Mukhlishotul Muhimmah, Aufia Aisa, Dian Kusuma Wardani (JIP: Jurnal Ilmu Pendidikan, 2024)
This research was motivated by the lack of MA Bahrul Ulum Jombang students in mastering Arabic, especially in speaking skills. This is because the learning process is not effective both in terms of learning methods and also textbooks that become a reference. Therefore, this study was conducted aimed at developing Arabic textbooks based on educational games of speaking skills as a solution to overcome the lack of mastery of Arabic speaking skills. The method used in this study is R&D by applying the ADDIE model. The subjects in this study were class X social studies students of MA Bahrul Ulum Jombang, totaling 29 children. The data instruments used are in the form of interviews, questionnaires, and tests. The types of data analyzed produce qualitative and quantitative data including: 1) teaching materials have been developed in the form of Arabic textbooks based on educational games of speaking skills. 2) Based on validity tests, the textbooks developed achieved a very valid feasibility level with an average of 93.33% of media experts and 85% of media experts. 3) the level of effectiveness of textbooks is very effective judging from the analysis using paired t-tests which get significant value results of 0.00 < 0.05 so it is said that there is an influence in the use of textbooks.